Blackcurrant Anthocyanins Attenuate Estrogen -Deficiency-Induced Bone Loss through Modulating Microbial-Derived Short-Chain Carboxylic Acids and Phytoestrogen Metabolites in Peri- and Early Postmenopausal Women - Briana M. Nosal; Staci N. Thornton; Alexey V. Melnik; Ali Lotfi; Manije Darooghegi Mofrad; Alexander Aksenov; Elaine Choung-Hee Lee; Ock K. Chun (Metabolites)
Objectives: The present study aimed to assess the effects of blackcurrant (BC) anthocyanins on concentrations of microbial-derived short-chain carboxylic acids (SCCAs) and metabolites of phytoestrogens. We then examined their associations with six-month changes in whole-body bone mineral density (BMD) and biomarkers of bone metabolism. Methods: Fecal and blood samples from a pilot randomized controlled trial were collected and analyzed from 37 eligible peri- and early postmenopausal women aged 45–60 years who were randomized into one of three treatment groups consuming one placebo capsule (control), 392 mg BC (low BC) or 784 mg BC (high BC) daily for six months. Results: Significant differences were observed between groups at baseline in acetic, propionic, valeric, caproic and heptanoic acids (p < 0.05). Isobutyric acid significantly decreased from baseline (0 months) to six months in the control group (p < 0.05) and the high BC group had a significantly greater concentration than the control group at six months (p < 0.05). Butyric acid was significantly greater in the high BC group than low BC at six months (p < 0.05). Six-month changes in caproic and isobutyric acids showed weak correlations with changes in whole-body BMD (r = 0.3519, p < 0.05 and r = 0.3465, p < 0.05, respectively). Isovaleric and valeric acids displayed weak correlations with BALP (r = 0.3361, p < 0.05) and OPG (r = 0.3593, p < 0.05), respectively. Enterodiol was positively correlated with BALP (r = 0.6056, p < 0.01) while enterolactone was positively correlated with osteocalcin (r = 0.5902, p < 0.001) and negatively correlated with sclerostin (r = −0.3485, p < 0.05). Conclusions: The results suggest that BC may be a potential dietary agent to reduce postmenopausal bone loss through modulating microbially-derived SCCAs and phytoestrogen metabolites.